A risk assessment model for Salmonella spp. in swine carcasses. (25th May 2022) - Chalias, Athanasios; Grispoldi, Luca; Cenci Goga, Beniamino
Abstract: Salmonellosis is one of the most important food‐borne outbreaks that occurs in the EU/EEA. From the first production stages at slaughter, meat is susceptible to spoilage and can be a substrate for the pathogenic microorganisms growth. Among the pathogens, the presence of Salmonella is mainly due to mishandling during the evisceration stage. For the year 2019, according to the collected data from MSs, on the 17.9% of all food‐borne outbursts, the presence Salmonella was confirmed. Pork meat is considered as one of the four most commonly reported foods in cases of salmonellosis. For the training purposes of this project, Salmonella isolation and identification along with RA for carcass contamination, was performed. Pig carcasses were sampled using the non‐destructive technique. The sampling took place post dressing and before the stage of chilling. For the Salmonella detection, a three phases process was performed (pre‐enrichment, enrichment, isolation). A total of 757 samples were collected, 19 were found to be positive for Salmonella . The most common was found to be Salmonella Derby, which was identified eight times. The main objective of the project was to determine the prevalence of Salmonella spp. in swine carcasses. Moreover, certain parameters were evaluated in terms of their influence on the prevalence of Salmonella . A stochastic simulation model was developed in Microsoft Office Excel 2019 by using the add‐in @Risk v.8.1. The prevalence was estimated to be 2.6%. For the pigs sampled, the average value of the distance from farm to slaughterhouse was 200.92 km. Additionally, the average weight of the carcasses was 127.97 kg. The prevalence of Salmonella between the samples that came from farms with a distance above the average, was higher by 1.7 units, while the prevalence for the samples with weight above the average was higher by 0.2 units. According to the stochastic model, it is specified that the prevalence is higher with greater distance, and there is an 8.1% probability the prevalence will exceed the legislation's – hygiene criteria. In addition, the prevalence of Salmonella was shown to increase, as well in the case of samples from weightier animals, but to a lesser extent.